Feasibility of Mouth-to-Mouth Ventilation through FFP2 Respirator in BLS Training during COVID-19 Pandemic (MOVERESP Study): Simulation-Based Study - Martina Kosinová; Petr Štourač; Tereza Prokopová; Tereza Vafková; Václav Vafek; Daniel Barvík; Tamara Skříšovská; Jan Dvořáček; Jana Djakow; Jozef Klučka; Jiří Jarkovský; Pavel Plevka (MDPI AG, 2022)
Background: Due to the COVID-19 pandemic, Basic Life Support (BLS) training has been limited to compression-only or bag-mask ventilation. The most breathable nanofiber respirators carry the technical possibility for inflation of the mannequin. The aim of this study was to assess the efficacy of mouth-to-mouth breathing through a FFP2 respirator during BLS. Methods: In the cross-over simulation-based study, the medical students performed BLS using a breathable nanofiber respirator for 2 min on three mannequins. The quantitative and qualitative efficacy of mouth-to-mouth ventilation through the respirator in BLS training was analyzed. The primary aim was the effectivity of mouth-to-mouth ventilation through a breathable respirator. The secondary aims were mean pause, longest pause, success in achieving the optimal breath volume, technique of ventilation, and incidence of adverse events. Results: In 104 students, effective breath was reached in 951 of 981 (96.9%) attempts in Adult BLS mannequin (Prestan), 822 of 906 (90.7%) in Resusci Anne, and 1777 of 1857 (95.7%) in Resusci Baby. In Resusci Anne and Resusci Baby, 28.9%/15.9% of visible chest rises were evaluated as low-, 33.0%/44.0% as optimal-, and 28.8%/35.8% as high-volume breaths. Conclusions: Mouth-to-mouth ventilation through a breathable respirator had an effectivity greater than 90%.